ANALISIS PROFITABILITAS OLAHAN KOPI ROBUSTA SEBAGAI PRODUK UNGGULAN KOPERASI TIRTO KENCONO DI KABUPATEN TANGGAMUS - Savitry, Laely; Endaryanto, Teguh; Murniati, Ktut (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This study aims to analyze income and profitability of processed robusta coffee as a superior product in Tirto Kencono Cooperative. The research method used in this study is a case study. Respondents in this study were manager, suppliers and all people related in the robusta coffee processing unit. The research was conducted at the Tirto Kencono Cooperative located in Talang 20 Village, Air Naningan Sub-District,Tanggamus District. Data collection was conducted in February 2019 and analyzed using quantitative descriptive analysis. The results of the research showed that the four products were viable and feasible because the R/C values were more than one on cash costs and total costs. Four products have profitability ratio of more than 0% with the highest profitability ratio was obtained by Green Coffee T20 product (77.40%) and the lowest product was Gendis Coffee T20 (21.24%). Key words : income, profitability, robusta coffee